Formulation of Ethanol Extract Cream of Sikkam Leaves (Bischofia javanica Blume) as an Antifungal Against Candida albicans - wulandari, Suci; Br Purba, Sri Ulina; Miranti; Zebua, Kristian Cahayani (Jurnal FARMASIMED (JFM), 2024)
Skin health issues in Indonesia, including those caused by fungal infections such as (Candida albicans), can lead to various conditions like candidiasis, scabies, tungiasis, and leprosy. This study aims to evaluate the potential of sikkam leaf extract in developing an antifungal cream to combat (Candida albicans). Fungi are eukaryotic organisms that cannot photosynthesize and reproduce through branching filaments composed of hyphae. Fungi can thrive in diverse environments such as water, soil, and decaying organic matter. A cream is a semi-solid emulsion preparation in which one or more medicinal substances are dissolved or dispersed within a base. This formulation determines the cream’s effectiveness, including the optimal ethanol extract concentration needed for antifungal activity. Extraction of sikkam leaves was conducted using maceration with 70% ethanol, and creams were formulated with extract concentrations of 5%, 10%, and 15%. Data were analyzed using the Kruskal-Wallis test. The study results showed that sikkam leaf-based creams meet quality standards, including organoleptic properties, homogeneity, pH, spreadability, and physical stability. Effectiveness testing indicated that creams with 5%, 10%, and 15% concentrations produced inhibition zones against (Candida albicans) with average diameters of 6.3 mm, 9 mm, and 15.3 mm, respectively. The higher the extract concentration, the stronger the inhibition of fungal growth. The cream with a 15% concentration proved to be the most effective, with inhibition classified as strong. Thus, sikkam leaf extract shows potential as a key ingredient for antifungal cream formulations.